2018
DOI: 10.1097/md.0000000000011185
|View full text |Cite
|
Sign up to set email alerts
|

Association between psoriasis and vitamin D

Abstract: Recent literature has focused on the association of psoriasis with lower than normal or highly deficient vitamin D blood levels.To investigate the controversial association between psoriasis and vitamin D levels.From 2012 to 2014, 561 subjects were assessed, of which 170 had psoriasis, 51 had an autoimmune bullous, and 340 were healthy patients. Anagraphical data, 25(OH)D blood levels, and seasons of vitamin D levels assessments were recorded for each group.Vitamin D levels were significantly different among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The 25-hydroxyvitamin D [25(OH)D] blood level in each group was measured and found to be significantly different in all three groups, with psoriatic patients having significantly lower vitamin D levels (21.8 ng/mL) than healthy controls (34.3 ng/mL) ( p = 0.0007). The authors of this study concluded that vitamin D level may correlate with psoriasis duration [ 131 ].…”
Section: Role Of Micronutrients In Scalp Scaling Conditionsmentioning
confidence: 99%
“…The 25-hydroxyvitamin D [25(OH)D] blood level in each group was measured and found to be significantly different in all three groups, with psoriatic patients having significantly lower vitamin D levels (21.8 ng/mL) than healthy controls (34.3 ng/mL) ( p = 0.0007). The authors of this study concluded that vitamin D level may correlate with psoriasis duration [ 131 ].…”
Section: Role Of Micronutrients In Scalp Scaling Conditionsmentioning
confidence: 99%
“…However, vitamin D has shown a relevant yet controversial role in psoriasis, as well as other skin diseases [ 43 , 44 ]. In this area, Filoni et al aimed to shed some light by confirming reduced vitamin D levels in psoriatic patients and stablishing a relationship between vitamin D levels and psoriasis length [ 45 ]. Moreover, Lee et al also confirmed lower presence of 25-hydroxyvitamin D (25OHD) in psoriasis patients, 25OHD being an possible indicator of the amount of stored Vitamin D [ 46 , 47 ].…”
Section: Current Marketed Therapiesmentioning
confidence: 99%
“…It is reported that serum vitamin D levels are reduced in patients with psoriasis or PSA compared to controls [ 52 , 53 ]. In addition, the decreased expression of vitamin D receptor in psoriatic skin is correlated with the reduced expression of tight junction proteins like claudins, occludins, or Zonula Occludens-1 [ 52 ].…”
Section: The Nutrients or Food Related To Psoriasismentioning
confidence: 99%